KRITIK SNOUCK HURGRONJE TERHADAP KOLONIALE VRAAGSTUKKEN VAN HEDEN EN MORGEN (1928) KARYA HENDRIKUS COLIJN - Wibisono, Gabriel Perigrinus Satrio; Sunjayadi, R Achmad (UI Scholars Hub, 2026)
Snouck Hurgronje was an Orientalist who had a different view from the colonial government regarding Indonesian independence. Snouck Hurgronje was always outspoken about the situation and dared to take action. This study discusses the views of Dutch and Flemish newspapers, namely Nieuwe Rotterdamsche Courant, Algemeen Handelsblad, and De Standaard, in their December 7 and 8, 1928 editions, regarding Snouck Hurgronje's criticism of Koloniale Vraagstukken Van Heden En Morgen (1928) by Hendrikus Colijn, an anti-revolutionary official. Snouck Hurgronje’s criticism of the Dutch government was viewed negatively. This study uses historical methods through the process of topic selection, source collection, verification (historical criticism, source validity), interpretation (analysis and synthesis), and historiography. The results show that Snouck Hurgronje could be rejected when his opinions conflicted with colonial political interests. The Dutch media's criticism of Snouck Hurgronje in 1928 reflected a political position that sought to maintain a way of thinking that was in line with that of the Dutch government.